An Example for Determining the Physical Parameters Used in DEM Modelling for the Interaction Process between Aggregates and Working Equipment - Niţă, A; Laudacescu, E; Ramadan, I N; Petrescu, M G (IOP conference series. Materials Science and Engineering, 2022)
Modern economies are based on an efficient communications and transport infrastructure. In this context, road networks make an essential contribution to the movement of large quantities of raw materials, finished products as well as to human transport for productive or recreational purposes. In order to maintain the optimal functioning of the road infrastructure, it is necessary to ensure high quality lanes. Road construction and maintenance work play an important role in supporting the ideas mentioned above. The used equipment for production of asphalt pavements (asphalt concrete) and their maintenance are the subject of numerous studies, proving the interest for this field. The authors of paper: An Example for Determining the Physical Parameters Used in DEM (Discrete Element Method) Modelling for the Interaction Process between Aggregates and Working Equipment, present an example for determining physical parameters that are used in specific numerical modelling of operation equipment which interacts with structures (drum dryer, mixer for concrete production and milling machine for asphalt pavement). In order to model the real phenomena in which granular materials are involved (cereals, mineral aggregates, and other powdery substances) it is very important to use not only appropriate software but also to use primary data to accurately characterize the phenomena. The sizes that characterize the interaction between particles and between particles and the space in which they move are very important. The study covers any type of granular material of mineral origin, in particular mineral aggregates used in the manufacture of concrete, cement or asphalt.